Contract cheating: a survey of Australian university students - Bretag, Tracey; Harper, Rowena; Burton, Michael; Ellis, Cath; Newton, Philip; Rozenberg, Pearl; Saddiqui, Sonia; van Haeringen, Karen (Studies in higher education (Dorchester-on-Thames), 2019)
Recent Australian media scandals suggest that university students are increasingly outsourcing their assessments to third parties - a behaviour known as 'contract cheating'. This paper reports on findings from a large survey of students from eight Australian universities (n = 14,086) which sought to explore students' experiences with and attitudes towards contract cheating, and the contextual factors that may influence this behaviour. A spectrum of seven outsourcing behaviours were investigated, and three significant variables were found to be associated with contract cheating: dissatisfaction with the teaching and learning environment, a perception that there are 'lots of opportunities to cheat', and speaking a Language Other than English (LOTE) at home. To minimise contract cheating, our evidence suggests that universities need to support the development of teaching and learning environments which nurture strong student-teacher relationships, reduce opportunities to cheat through curriculum and assessment design, and address the well-recognised language and learning needs of LOTE students.